Letter - Negrín, Juan
1942-12-09 013-0009-001 J. NEGRIN Bovingdon, 9.12.1942. Your ref: International. WMC/WJB/DT/365. Private. Dear Sir Walter, Thank you very much for your letter of December 1st., infoming me that Largo Caballero and the other Republican leaders have not been extradited, and that the probability is that they will not be handed over to the Spanish Government. I need hardly say how relieved we are to have this news, and I am most grateful to you for sending it to me. Yours sincerely, Negrin Sir Walter Citrine, K.B.E., Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/13/9(i)